Time-resolved UV spectroscopy of the accretion disk and wind in a super-Eddington black-hole X-ray transient - Castro Segura, Noel; Knigge, Christian; Long, Knox S.; Altamirano, Diego; Armas Padilla, Montserrat; Casares, Jorges; Charles, Philip A.; Degenaar, Nathalie; Fender, Rob; Gandhi, Poshak; Hernandez Santisteban, Juan Venancio; Higginbottom, Nick; et al. (HST Proposal, 2019)
In October 2018, Swift announced the discovery of a new Galactic X-ray transient, Swift J1858. Just before Sun-angle constraints rendered the system unobservable, follow-up observations revealed extreme flaring activity, of a kind that has so far only been seen in the famous black hole X-ray binary (BHXRB) V404 Cyg during its 2015 eruption and in V4641 Sgr. The peculiar behaviour of these sources is thought to be a consequence of super-Eddington accretion regime. After several months of unusual strong and rapid flaring in its high-luminosity state, Swift J1858 is currently exhibiting impressive optical P-Cygni profiles, suggesting the pres- ence of a dense and cool wind from the outer accretion disk. The dominant spectroscopic signatures of such winds are actually expected to lie in the far-ultraviolet region, but they are usually inaccessible in black-hole X-ray binaries, due to interstellar reddening. Given its low extinction, Swift J1858 provides us with a rare chance to study the accretion disk wind in the crucial ultraviolet band - an opportunity that was missed in the other two systems. Building on an ongoing multi-wavelength campaign (X-rays: NICER; optical: GTC; radio: VLA & AMI), we therefore request far- and near-UV time-resolved spectroscopic observations of this system with HST/STIS+COS in order to (a) study its extreme accretion disk wind; (b) test proposed wind driving mechanisms; (c) characterize its UV variability properties and determine the origin of these variations; (d) construct the broad-band SED of the outer accretion disk that dominates the UV flux; and (e) determine the extinction towards the system in order to constrain the mass accretion rate.